The control of Latin American trypanosomiasis - Philip D. Marsden (Revista da Sociedade Brasileira de Medicina Tropical, 1997)
The author presents his personal point of view on the present situation of Chagas' disease control in Latin America countries. He compares the situation with African trypanosomiasis. He comments on the existence of cases in other Continents. He emphazises the success of the fighting against domiciliated triatomine bugs by using residual inseticides. He discusses other forms of Trypanosoma cruzi transmission. O autor apresenta seu ponto de vista pessoal sobre a situação atual do controle da doença de Chagas nos países da América Latina. Compara a situação com a tripanossomíase africana. Comenta a existência de casos em outros Continentes. Acentua o êxito da luta contra os triatomíneos domiciliados, através do uso de inseticidas residuais. Defende outras formas de transmissão do Trypansoma cruzi.